Determinação voltamétrica de mancozebe em hortaliça utilizando eletrodo modificado com pontos quânticos de carbono/β-ciclodextrina - Amaral, Mateus Ferreira (2024)
The broad-spectrum fungicide mancozeb is employed to protect fruits and vegetables from foliar diseases and is used to protect such products during their storage and transportation. It is Brazil's fourth most utilized pesticide and has raised increasing concerns due to potential health risks. Given the widespread use of mancozeb and the limited number of studies employing electroanalytical methods for its quantification, this dissertation proposes the development of an electrode modified with carbon quantum dots (CQDs) and β-cyclodextrin (ßC) for voltammetric detection of mancozeb in Swiss chard samples. N and S-functionalized CQDs were obtained by the thermal decomposition of citric acid and L-cysteine and characterized by UV/VIS spectroscopy, presenting two distinct absorption bands at 250 nm and 340 nm, characteristic of these nanomaterials. Fluorescence analyses evidenced an emission band at 410 nm when excited at 340 nm, resulting in a quantum yield of 58.2%. The modification of glassy carbon electrodes was carried out via the electrochemical deposition of CQDs in a ßC medium. In the electrochemical characterization of the electrodes by impedance spectroscopy, a semicircle was observed for the ßC/GCE, CQDs/GCE, and ßCCQDs/GCE electrodes in the high-frequency region, indicating that the materials were successfully deposited on the electrode surface. Voltammetric studies evidenced an oxidation process for MCZB, with a peak potential at 0.67 V (vs. Ag/AgCl), showing an analytical signal gain for the ßCCQDs/GCE modified electrode. For the quantification of MCZB, the square wave voltammetry technique parameters were optimized using a 0.1 molL-1 phosphate buffer solution (pH 7.0) as the supporting electrolyte. The method presented a linear range of 1.1 mgL-1 to 28 mgL-1 (n= 8, r= 0.9918), with detection and quantification limits of 0.9 mgL-1 and 2.70 mgL-1 , respectively. The method was applied to Swiss chard samples, obtaining recovery values between 83.8% and 107.3% for three fortification levels, with a relative standard deviation below 6%, demonstrating that the proposed electrochemical method determining accurately MCZB, without the need for derivatization of the fungicide molecule.